Cross cultural study on the influence of the ethnicity of the sexual image on perceptions towards sexual appeal ads. - Foo, Lee Hoon. (2008)
This study seeks to investigate whether Asians/Westerners perceive Asians/Westerners to be more suitable for sexual-appeal ads, sexier, classier and have stronger sex appeal. We will examine the influence of culture, ethnicity of the sexual image and gender on consumers’ perceptions towards sexual-appeal ads.